Unwitting adult marijuana poisoning: a case series - Fong, Kelly; Hsueh, Andy; Kendric, Kayla; Kunihira, Karissa; Siddiqi, Nadia; Phan, Tammy H.; Reibling, Ellen; Wolk, Brian J. (Clinical toxicology (Philadelphia, Pa.), 2021)
With increasing state legalization, marijuana use has become commonplace throughout much of the United States. Existing literature on unintentional exposure focuses primarily on children. We report on a cluster of adults with unwitting marijuana exposure. A cluster of cases were referred to the Medical Toxicology Service after ingesting marijuana-contaminated food at a family event. We conducted a retrospective analysis of twelve subject charts and a qualitative analysis with six of these subjects who willingly consented to be interviewed about their experiences. The study was approved by the Institutional Review Board. Three of the subjects (25%) required prolonged observation due to persistent symptoms. Eleven (92%) were urine immunoassay positive for tetrahydrocannabinol (THC). Two subjects (17%) tested positive for ethanol in their blood. Common symptoms experienced by the subjects included confusion (50%), difficulty speaking (67%), nausea (25%), tremors (17%), and feelings of unreality (33%). All interviewed subjects reported sleepiness and three (50%) reported a negative impact on work. Subjects also reported multiple emotions, including anger, confusion, disbelief, and helplessness. None of the cases resulted in admission for critical care or death. Our series illuminates effects of unwitting and/or unintentional marijuana exposure in adults. Unintentional marijuana poisonings have increased, but legal and regulatory barriers have limited the study of marijuana outside highly controlled conditions. While the marijuana exposure in this study did not result in admission for critical care or death, it did result in psychological distress and adversely affected work in some cases.